Slot-die coating of niobium pentoxide applied as electron transport layer for perovskite solar cells - Affonço, Lucas J. [UNESP]; Fernandes, Silvia L.; Assunção, João P.F. [UNESP]; Dagar, Janardan; Graeff, Carlos F. de O. [UNESP]; da Silva, José H.D. [UNESP]; Unger, Eva (Elsevier, 2024)
Despite their high efficiency, perovskite solar cells encounter stability issues and necessitate techniques capable of depositing large areas at a high throughput of their layers. Niobium pentoxide exhibits pertinent characteristics, including suitable energy level alignment and photostability for effective integration as transport layer in perovskite solar cells, improving their stability. In this study, the deposition of Nb2O5 as an electron transport layer via slot die coating is systematically investigated. An examination of various parameters for the slot die coating process was conducted, resulting in films with different structural and morphological characteristics. These Nb2O5 layers were used as electron transport layers in n-i-p perovskite devices. Current density versus voltage scans were utilized to evaluate the device performance, alongside transient analysis. Under optimal coating conditions, efficiencies up to 12 % were obtained. A transient analysis at the maximum power point identified an optimal delay time of approximately 200 ms for integration into the current–voltage curves, facilitating the approach towards an equilibrium state within the device. A discussion regarding the transient response is presented, delving into the factors that restrict the device's performance and proposing potential strategies for its enhancement.
Keywords: Niobium oxide; Perovskite solar cell; Slot die coating; Transport layer